Influence of air on heat transfer of a closed-loop spray cooling system - Liu, Pengfei (2022)
The influence of air must be considered when designing a direct spray cooling system for electronics because of its inevitable existence. In the present study, the influence of air on spray cooling is experimentally investigated with the air volume concentration ranging from 0.06 to 0.65 and the chamber total pressure from 0.44 bar to 1.07 bar. Two dielectric fluids (PF-5060 and FC-3284) are studied due to their compatibility with electronics. The results show that in the current experimental range the spray cooling is mainly affected by the liquid subcooling and surface superheat when air is present. The chamber total pressure appears to have a negligible influence on the spray cooling heat transfer, which differs from the spray cooling behavior without air. This argument holds true from the incidence of nucleate boiling to near the transition boiling regime as long as there is a sufficient amount of air present in the system. The air-entrainment-induced secondary nucleation can possibly leads to the insensitivity of the spray cooling heat transfer to the system pressure. A correlation is developed by incorporating the influence of the spray characteristics, the liquid properties, the chamber pressure, the degree of liquid subcooling, and the surface superheat. It provides a good prediction of the heat transfer rate for air-present spray cooling under current experimental conditions.